Problematizing Replicable Design to Practice Respectful, Reciprocal, and Relational Co-designing with Indigenous People. (2nd January 2019) - Akama, Yoko; Hagen, Penny; Whaanga-Schollum, Desna
Abstract: Designing among Indigenous and non-Indigenous people is turbulent because we are all working within differing legacies of colonialism and entrenched systems of "othering." When design enters this space through widely popular methods like the Double Diamond or Human-Centered Design (HCD) toolkits, it often carries legacies of its industrialized, Eurocentric origins. These origins emphasize problem-solving, replicable methods and outcomes, pursue simplicity and efficiency, and detach knowledge, people, and relationality from the sites of design's embodiment. This risks perpetuating acts of colonialism, inadvertently displacing Indigenous practices, knowledges, and world views. Instead, we propose respectful, reciprocal, and relational approaches as an ontology of co-designing social innovation. This ontology requires a sensitivity to design's location within multi-layered sites of power, knowledge, practices, cultural values, and precarious asymmetries as the condition of collaboration. We provide personal, reflexive stories as Māori, Pākehā, and Japanese designers negotiating the legacies of colonialism, laying bare our whole selves to show accountability and articulate pluralities of practices. In respecting design that is already rooted in local practices, we learn from these foundations and construct our practices in relation to them. For us, respect, reciprocity, and relationships are required dimensions of co-design as an engaged consciousness for Indigenous self-determination.